Nowe materiały z tzw. fazy wielkowiejskiej w Orliku, gm. Brusy, stanowisko 4 - Walenta, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
The site at Orlik is located in the so-called Leśno microregion, which has been investigated for several years by the Archaeological Expedition of Łódź University. Of the 4 graves recorded on the site the first has been totally destroyed by building operations. Finds from another grave, also revealed during building works, have found their way to the Expedition and proved to represent forms rarely encountered in this part of Pomerania, and typical of the so-called Wielka Wieś phase of Hallstatt С. Excavations conducted in the region of the first two graves have yielded another two burials: no 3, well preserved and no 4, damaged. Pottery from the graves is typical of Hallstatt С. On the other hand, undisturbed grave no 3 was unique in from. Its bottom and the walls of the burial chamber were built of field stones, while the vessels put inside the chamber were covered with a loose stone pavement. This grave is closest in form to the so-called stone-set graves. The site is an important addition to archaeological sources in the Leśno microregion and in the whole southern part of East Pomerania.